CATalytic Insurance : The Case of Natural Disasters - Cordella, Tito; Yeyati, Eduardo Levy (2012)
Why should countries buy expensive catastrophe insurance? Abstracting from risk aversion or hedging motives, this paper shows that catastrophe insurance may have a catalytic role on external finance. Such effect is particularly strong in those middle-income countries that face financial constraints when hit by a shock or in its anticipation. Insurance makes defaults less appealing, relaxes countries' borrowing constraint, increases their creditworthiness, and enhances their access to capital markets. Catastrophe lending facilities providing "cheap" reconstruction funds in the aftermath of a natural disaster weaken but do not eliminate the demand for insurance.